Handling Information for Learning Disability Workers / Supporting the Level 2 and 3 Diplomas in Health and Social Care (Learning Disability Workers) and the Common Induction Standards - Barcham Lesley; Pountney Jackie (Learning Matters, 2011)
This book puts the person with a learning disability at the center of the support you give. Introduction, Understanding Requirements for Handling Information in Health and Social Care Settings, Maintaining Records in Line with Agreed Ways of Working, Supporting Others to Handle Information, Glossary, Index.